Upaya Meningkatkan Hasil Belajar Mata Pelajaran PAI Melalui Model Sharing dan Media Audio Visual Pada Materi Beriman Kepada Malaikat Siswa Kelas V SD Negeri 06 Tarung-Tarung - Elmita, Elmita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) on the material "Belief in Angels" through the implementation of the sharing learning model and audio-visual media. The research was conducted at SD Negeri 06 Tarung-Tarung with 9 fifth-grade students. This study uses a Classroom Action Research (CAR) design carried out in two cycles. The results indicate that the implementation of the sharing model and audio-visual media can enhance students' learning outcomes. In Cycle I, 77.2% of students achieved mastery, while in Cycle II, 100% of students achieved mastery. Additionally, student activity showed significant improvement, with 100% of students actively involved in the learning process. Thus, this learning model proved effective in improving learning outcomes and student engagement.